Bentuk Dan Fungsi Ragam Hias Pada Pendapa Sasana Sewaka Di Keraton Kasunanan Surakarta joko Budiwiyanto - joko Budiwiyanto (Gelar : Jurnal Seni Budaya, 2007)
This Article represent result of conducted by research at Sasana Sewaka  pendapa in Keraton Surakarta. used by Type Research is qualitative by using approach  of hermeneutik. From result of analysis can be conduded, that classified decorative  manner form to become geometric form, flora, fauna, calligraphy, and other jorms.  location of decorative Manner, classified to become two, that is decorative manner  which have the character of constructive and decorative manner which have the character  of patching. Function from decorative manner is as building element decorator, sacral  function symbolic, and social junctionKeyword: Form, Function, Decorative Manner.